Research progress and strategies for multifunctional rapeseed: A case study of China - Dong-hui FU; Ling-yan JIANG; Annaliese S Mason; Mei-li XIAO; Long-rong ZHU; Li-zhi LI; Qing-hong ZHOU; Chang-jian SHEN; Chun-hui HUANG (Journal of Integrative Agriculture, 2016)
Rapeseed (Brassica napus), is an important source of edible oil, animal fodder, vegetables, condiments and biodiesel, and plays a significant role in securing edible oil production worldwide. However, in countries with comparatively low levels of agricultural mechanization, such as China, increasing costs of labor and agricultural inputs are decreasing rapeseed profitability, and hence the area of rapeseed under cultivation. If the value of rapeseed crops is not further increased, the rapeseed growing area will continue to decrease, potentially jeopardizing oil production. Therefore, full exploitation of the existing and potential value of rapeseed is desirable. Different rapeseed products are already utilized in different ways, with more applications currently underutilized. As well as oil extraction from the seeds, the shoot and leaves can be used as vegetables, the roots to absorb soil cadmium for pollution remediation, the flowers for sightseeing and as a source of nectar, the pollen for extracting flavonoids and useful amino acids, the seeds/seed meal for extracting isthiocyanates and other important sulforaphane compounds, the straw and seed meal for fodder, and immature whole plants for green manure. This review summarizes recent research on ways to explore the potential holistic value of rapeseed, by taking the example of multifunctionality of rapeseed in China.